Daya Saing Eskpor Kopi Indonesia di Pasar Internasional - Putra, Angga Dwi Kelana; Sibuea, Mhd. Buhari; Noer, Zulheri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Indonesia's export value has decreased while Indonesia's coffee production has increased. Competition in seizing the current market in order to increase and maintain the quantity or volume of exports in the international market. The increase is to be able to compete in the international market to be able to excel with other countries as well as various challenges faced and in an effort to increase the volume and value of coffee commodity exports with competitiveness and demand for coffee in the international market. Researchers aim to analyse the export of HS 0901 coffee commodities to the largest destination countries exporting to Egypt , Malaysia, Italy and Japan, although in this case the volume of coffee exports has decreased. This research is a time series secondary data collection based on 2018 to 2023. The export data studied is the export of coffee commodities with the code (Harmonized System) HS 0901 to Malaysia, Japan, Egypt and Italy using Revealed Comparative Advantage Analysis and Trade Specialisation Index. The results show that HS 0901 coffee has strong competitiveness comparatively in Malaysia, Egpy and Japan. While in Italy the RCA value does not have comparative competitiveness. In ISP Indonesia is at the maturity stage by producing an average ISP Value of 1.